The Symbolism of the Journey in Sufi Discourse: Al-Isrāʾ ilā Maqām al-Asrā or The Book of the Miʿrāj by Ibn ʿArabi as a Model - bouchelaleg, hakima.; labcir, samra (El Omda in Linguistics and Discourse Analysis, 2018)
The Sufi journey toward the Absolute forms the foundation of the Sufi experience, serving as the symbolic counterpart to that experience. Both classical and contemporary Sufis have used various terms to describe this imagined journey, often conveyed through elements of narrative and suspense. It closely resembles a narrative text, with its own stages and states, and it varies from one Sufi to another. For Sufis, its beginning is linked to spiritual practice, detachment from anything that binds the seeker’s self to the world and its pleasures, and liberation from the desires, passions, and temptations of the ego. Historically, Sufis were called “strangers” because of this journey—their path toward the Absolute Self. A Sufi attains knowledge only in proportion to their estrangement from the self, and the purpose of this estrangement is to minimize the ego’s attachment to worldly matters and sever ties with the lustful self, allowing the spirit to ascend toward higher realms purified of its attributes.